Inhibition of Caspase-1 Ameliorates Ischemia-Associated Blood-Brain Barrier Dysfunction and Integrity by Suppressing Pyroptosis Activation - Liang, Yubin; Song, Pingping; Chen, Wei; Xie, Xuemin; Luo, Rixin; Su, Jiehua; Zhu, Yunhui; Xu, Jiamin; Liu, Rongrong; Zhu, Peizhi; Zhang, Yusheng; Huang, Min (Frontiers in Cellular Neuroscience, 2021)
Ischemic cerebral infarction represents a significant cause of disability and death, worldwide. Caspase-1 is activated by the NLRP3/ASC pathway and inflammasomes thus triggering pyroptosis, a programmed cell death. In particular, this death is mediated by Gasdermin D (GSDMD), which induces secretion of IL-1β and IL-18. Accordingly, inhibition of caspase-1 prevents the development and worsening of multiple neurodegenerative diseases. However, it is not clear whether inhibition of caspase-1 can preserve blood-brain barrier (BBB) integrity following cerebral infarction. This study therefore aimed at understanding the effect of caspase-1 on BBB dysfunction and its underlying mechanisms in permanent middle cerebral artery occlusion (MCAO). Our findings in rat models revealed that expression of caspase-1 was upregulated following MCAO induced injury in rats. Consequently, pharmacologic inhibition of caspase-1 using vx-765 ameliorated ischemia-induced infarction, neurological deficits and neuronal injury. Furthermore, inhibition of caspase-1 enhanced the encapsulation rate of pericytes at the ischemic edge, decreased leakage both of Evans blue (EB) leakage and matrix metalloproteinase proteins (MMPs), and upregulated the levels of tight junctions (TJs) and tissue inhibitor of metalloproteinases (TIMPs) in MCAO-injured rats. This in turn improved the permeability of blood-brain barrier. Meanwhile, vx-765 blocked the activation of ischemia-induced pyroptosis and reduced the expression level of inflammatory factors such as caspase-1, NLRP3, ASC, GSDMD, IL-1β and IL-18. Similarly, vx-765 treatment significantly reduced the expression levels of inflammation-related receptor for advanced glycation endproducts (RAGE), high-mobility group box 1 (HMGB1), mitogen-activated protein kinase (MAPK) and NF-κB. Evidently, inhibition of caspase-1 significantly improves ischemia-associated BBB permeability and integrity by suppressing pyroptosis activation and RAGE/MAPK pathway.